Get Acquainted with Quantile Regression - Agung Santoso; Tri Hayuning Tyas (ANIMA Indonesian Psychological Journal, 2016)
This article was written to introduce quantile regression (QR) analysis technique for research in Psychology. The authors present the advantages possessed by QR compared with ordinary least square (OLS) for the regression analysis approach. The QR’s main advantage than OLS is the information concerning the effects of the independent variables on the dependent variable at a location other than the mean. QR can also provide information regarding the effect of independent variables on the distribution and skewness of the dependent variable. Another QR’s advantage is associated with the robustness against violations of assumptions about the normal distribution of data and homogeneity of variance. These two advantages make the authors feel the need to introduce QR in studies in Psychology. The authors are then applying the QR on real data as an illustration. The results of the analysis in the illustration show the advantages of QR over OLS, especially in providing information on the phenomenon under study.